Metaverse in Education for AI-Enhanced Lifelong Learning and SDG Advancement in the Context of an Aging Society: A Systematic Review - Lumdee, Narong (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The rapid advancement of immersive technologies and Artificial Intelligence (AI) has reshaped digital education and introduced new possibilities for lifelong learning in aging societies. This study presents a systematic review of research published between 2020 and 2026 examining the integration of AI within Metaverse-based educational environments. Guided by the PRISMA framework, 18 peer-reviewed studies were identified and synthesized to analyze emerging research trends, pedagogical applications, and alignment with the Sustainable Development Goals (SDGs). Findings indicate a shift from technological infrastructure integration toward pedagogically focused applications, including intelligent tutoring systems, adaptive learning models, generative AI, and immersive simulations. AI enhances personalized learning pathways, real-time feedback, and experiential skill development within interactive virtual environments, supporting flexibility, self-directed learning, and continuous reskilling. The review further demonstrates strong alignment with SDG4 (Quality Education), SDG9 (Industry, Innovation, and Infrastructure), and SDG10 (Reduced Inequalities), highlighting the structural role of AI-enhanced Metaverse systems in promoting inclusive and sustainable educational ecosystems. Within the context of an aging society, immersive AI-driven environments show potential to mitigate mobility constraints, reduce social isolation, and foster cognitive engagement among older adults. AI-integrated Metaverse education represents an emerging paradigm capable of supporting inclusive, adaptive, and sustainable lifelong learning infrastructures in response to demographic transformation and global sustainability agendas.